LAYPERSON EDUCATION IN BASIC LIFE SUPPORT: IMPACT OF SHORT COURSES ON EARLY DETECTION OF CARDIOPULMONARY ARREST AND EMERGENCY RESPONSE - da Silva Borges, Alexander; Antonio Plautz Chocron, Marco (Health and Society, 2026)
Out-of-hospital cardiopulmonary arrest (OCA) is a high-mortality event, and survival critically depends on the immediate intervention of bystanders. The participation of the lay population in basic life support (BLS) actions is therefore essential to increase survival rates. This study will investigate the educational impact of short BLS courses, taught by nurses, academic institutions, and fire departments, on the training of laypeople. The research will adopt a mixed-methods design, integrating a quantitative assessment of knowledge and skills (pre- and post-training) with a qualitative analysis of the psychosocial factors that modulate the willingness to intervene. Variables such as early recognition of CPA, appropriate activation of emergency services, quality of chest compressions (depth, frequency, chest recoil), and correct use of an automated external defibrillator (AED) will be examined. The study will also consider factors such as self-confidence, anxiety, perceived barriers, and motivation. Expected outcomes include validating short courses as an effective tool for increasing public confidence and competence, expanding community response to emergencies, and strengthening health education policies aimed at reducing cardiac arrest mortality, aligned with international resuscitation guidelines.